Natural pigment based on orange fruit for superhydrophobic dyeing in cotton knitted textile application - Marsi, Noraini; Tan, Ka Seng; Thana Singam, Rupashinii; Mohd Rus, Anika Zafiah; Abdul Rashid, Azrin Hani; Main, Nor Mazlana (Engg Journals Publications, 2018)
The study of pigment based on orange fruits for superhydrophobic dyeing in cotton knitted textile applications. The synthetic pigment is replaced by orange fruit pigment to apply into cotton knitted textile applications in this study. The main objective of this study formulates and synthesis the orange fruit pigment for superhydrophobic dyeing and evaluate the mechanical and physical test for superhydrophobic dyeing in cotton knitted textile applications. The orange fruit pigment was extracted and used to dye the cotton knitted fabric in different concentration of orange fruit pigment which is 20%, 40%, 60% and 80%. Then, the cotton knitted fabric is sprayed by the superhydrophobic solution. The component of dyeing was involved pigment, solvent, binder, additive, and hardness. All the dyeing components have been synthesis to apply superhydrophobic dyeing in cotton knitted textile applications. A few physical and mechanical tests are conducted on the sample. In the water droplets test (ASTM D5946-04), the 60% of orange fruit pigment had the excellent superhydrophobic properties which are 151° of water droplet surface contact angle. For the colourfastness to crocking test (ASTM D5053), all the fabric had the same dry crocking result which is reading of 5. In wet crocking result, the 80% of orange fruit pigment that applied to the fabric without superhydrophobic coating had a highest degree of colour transferred which is reading of 3.5. For the bursting strength test (ASTM D3786), the 80 % of orange fruit has the highest bursting strength which is 42.97 kPa for coated fabric and 41.78 kPa for fabric without superhydrophobic coating. For the abrasion resistance test (ASTM D4966-98), the 0% of orange fruit pigment that applied to the fabric without superhydrophobic coating has the highest percentage of weight loss which is 21.05% in 2500 times of rubbing. The combination of the concentration of 60% orange pigment and solution can be applied on cotton fabric due to its good mechanical and physical effect on the cotton knitted fabric surfaces and produced the optimum for the ability of superhydrophobic characteristic.